Formulation and in vitro evaluation of floating tablets of cephalexin using natural polymers - SWAPNA .R,; Dr. SHAILAJA .P,; Dr. BASAVA RAJU .D, (International Journal of Pharma and Bio Sciences, 2019)
Floating tablets of cephalexin were prepared using Albizia gum, Dammar gum and Moi gum as polymers for controlling the drug release. It was observed that cephalexin has good absorption in the GIT with a bioavailability of 95%. But the half life of the drug was found to be 1.1 hr this leads to the incorporation of the drug for 3-4 times a day, In order to maintain the therapeutic range. The solution for the above problem was resolved by making it into extended release tablet. Hence, number of attempts were made to increase their effectiveness and simultaneously reduce their doses and hence the toxic effects. Two types of diluents were used and the drug release was compared. Pure drug and optimized formulation were subjected to the drug excipient compatibility studies using FTIR and DSC. The studies revealed that there was no interaction between the drug and excipients. In order to increase the drug release, channeling agents were introduced namely Lactose and DCP. Lactose is a water soluble diluent and DCP is water insoluble diluent. Precompression parameters were performed to all the formulations and were found to be in the acceptable limit which ensures the good flow properties. Formulation F4CPDL containing gum dammar and lactose as channeling agent showed good results when compared to other formulations. The floating lag time of the optimized formulation was very short and the percentage of drug release at the end of 12 hours was found to be high. The drug release kinetics revealed that formulation F4CPDL follows Zero order.